The Relationship Between Genital Self-Image and the Quality of Sexual Life in Married Turkish Women. - Çataloluk, Ayşe; Eroğlu, Vasviye (Sexuality & Culture, 2025)
In recent years, there are studies in the literature showing that genital self-image and sexuality-related issues are related. Genital self-image and women's perceptions of sexuality vary in different cultures and societies. This study aimed to investigate the relationship between genital self-image and the quality of sexual life of married Turkish women. We conducted a descriptive and correlational study between June 15, 2023 and August 15, 2023, with 232 married women. The data were collected online using the Personal Information Form, The Female Genital Self‑Image Scale (FGSIS), and the Sexual Quality of Life Questionnaire-Female (SQLQ-F). Data analysis was performed through parametric tests, correlation and regression analysis. The mean scores of FGSIS and SQLQ-F were found to be 18.68 ± 4.19 and 75.11 ± 23.32, respectively. In the correlation analysis, a positive moderate-level significant relationship was determined between the total FGSIS score and the total SQLQ-F score (p < 0.001). A statistically significant difference was identified between the mean score of the FGSIS and women's and their husband's educational status, employment status of both women and husbands, delivery status, type of marriage, and self-perception of weight (p < 0.05). A statistically significant difference was detected between the mean score of the SQLQ-F and women's and their husband's educational status, income-expenditure level, delivery status, type of marriage, and self-perception of weight (p < 0.05). The genital self-image of the women is positive, and their sexual quality of life is good. It has been determined that as women's genital self-image increases, their quality of sexual life also increases. It is recommended that health professionals also evaluate genital self-image in their attempts to improve women's sexual life quality.